Pengembangan Bisnis Pada Kelompok UMKM “Mutiara Subur Jaya” - Encep Saefullah; Rika Kartika; Popi Dayurni (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The problems in the “Mutiara Subur Jaya” MSMEs Group are 1) The production process is still done manually and there is no press machine, so the products produced are not standardized; (2) There are not many variations in the product model; (3) The number of sewing machines owned is still lacking; (4) They do not yet have a NIB and IUMK; (5) The knowledge and skills of Partner HR in business management are still limited; (6) The financial recording system is still manual; (7) Partner skills in marketing are still minimal, and (8) The sales method is still conventional, not using digital media. By implementing the chronological method, this activity resulted in an increase in the number of production and sales of partner products by 75%, an increase in partner knowledge and skills by 68.05%, and the acquisition of legal operational business legality in the form of NIB and IUMK, so that the business of this MSMEs Group also developed.